2019
DOI: 10.18203/2319-2003.ijbcp20193174
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of ethanolic and aqueous extract of Turnera aphrodisiaca leaves against CCl4-induced liver injury in rats

Abstract: Background: The botanical Latin name of the plant, Turnera aphrodisiaca, describes its ancient use as an aphrodisiac.Methods: The aim of the present study is to evaluate the protective effect of ethanolic and aqueous extract of Turnera aphrodisiaca leaves against carbon tetrachloride (CCl4)-induced liver damage in male Wistar rats.Results: Administration with ethanolic and aqueous extract of Turnera aphrodisiaca leaves (200 and 400 mg/kg) for 7 days significantly reduced the impact of CCl4 toxicity on the seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…At the end of the study, they found a significant reduction in ALT, AST, and ALP levels in the groups treated with the extracts compared with the untreated groups. In contrast, SOD and CAT activity significantly increased [28]. Similar results were obtained with the ethanolic extract by employing an ethanol damage model and increasing the treatment period to 21 days, in addition to decreasing total bilirubin levels.…”
Section: Hepatoprotectionsupporting
confidence: 79%
See 1 more Smart Citation
“…At the end of the study, they found a significant reduction in ALT, AST, and ALP levels in the groups treated with the extracts compared with the untreated groups. In contrast, SOD and CAT activity significantly increased [28]. Similar results were obtained with the ethanolic extract by employing an ethanol damage model and increasing the treatment period to 21 days, in addition to decreasing total bilirubin levels.…”
Section: Hepatoprotectionsupporting
confidence: 79%
“…Table 5 includes mostly studies whose main objective was not to evaluate antioxidant activity. However, these studies show the ability of the extracts to modulate the activity of antioxidant enzymes [28], in addition to decreasing the levels of lipid peroxidation and cell damage caused by the generation of free radicals and reactive oxygen species [27,30]. Therefore, Tables 1-5 may include results not discussed in this section but will be addressed later.…”
Section: Introductionmentioning
confidence: 99%